2012
DOI: 10.1080/1406099x.2012.10840517
|View full text |Cite
|
Sign up to set email alerts
|

What managers think of capital structure and how they act: Evidence from Central and Eastern Europe

Abstract: This paper analyzes the capital structure and the choice of financing alternatives across a broad sample of Central and Eastern European companies. Our investigation is built on two methods: the first concentrates on capital structure decisions through quantitative information applying panel regression for the period 2005-2008 to allow a closer look at the strength of the pecking order and static tradeoff theories; and the second extends the analysis with a qualitative questionnaire on the explicit and latent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
2
17
1
Order By: Relevance
“…The empirical result found out that optimal capital structure is not a single point rather a range of values from zero to the industry and typical U.S. enterprises will only adjust to the optimal capital structure when the enterprises' debt level is out of this range. An extensive questionnaire for central and European countries was contented in the study of Hernádi and Ormos (2012), who found that CFOs present rather strong Pecking Order behaviour, with a limited role for target leverage. However, according to the results, trade-off theory and Pecking Order theory are not mutually exclusive.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The empirical result found out that optimal capital structure is not a single point rather a range of values from zero to the industry and typical U.S. enterprises will only adjust to the optimal capital structure when the enterprises' debt level is out of this range. An extensive questionnaire for central and European countries was contented in the study of Hernádi and Ormos (2012), who found that CFOs present rather strong Pecking Order behaviour, with a limited role for target leverage. However, according to the results, trade-off theory and Pecking Order theory are not mutually exclusive.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Companies prefer fi nancing from internal sources (from retained profi t) and only when there is not enough retained profi t, they use bank credits. It is also confi rmed by study by Hernandi and Ormos [9]. It states that in the Czech Republic (72 companies were represented) the managers claimed that for asset fi nancing they preferably use internally created fi nance sources.…”
Section: Compilation Of Hypotheses On the Basis Of Current State Of Kmentioning
confidence: 60%
“…Symbols and are the constant of the model and residual part in the GMM model. The reason for choosing the above mentioned indicators also comes from the performed studies (such as Nivorozhkin [16], Hernardi & Ormos [9], Crnigoj & Mramor [4], Růčková [20], Růčková & Heryán [21]) that considered particularities of the European environment, mainly weaker availability of the market data. It is just the unavailability of the market data that makes it impossible to apply studies performed in the United Stated of America as most of their models mainly use the market value of the company as a factor.…”
Section: Analysis Of the Functional Relation Of The Building Industrymentioning
confidence: 99%
“…The empirical result found out that optimal capital structure is not a single point rather a range of values from zero to the industry and typical U.S. enterprises will only adjust to the optimal capital structure when the enterprises' debt level is out of this range. An extensive questionnaire for central and European countries was contented in study of Hernádi and Ormos (2013), who find that CFOs present rather strong Pecking Order Behaviour, with a limited role for target leverage. However, according to results, Trade-off Theory and Pecking Order Theory are not mutually exclusive.…”
Section: Theory and Hypothesesmentioning
confidence: 99%